Do stage of disease, comorbidity or access to treatment explain socioeconomic differences in survival after ovarian cancer? – A cohort study among Danish women diagnosed 2005–2010. Issue 3 (June 2015) - Ibfelt, Else Helene; Dalton, Susanne Oksbjerg; Høgdall, Claus; Fagö-Olsen, Carsten Lindberg; Steding-Jessen, Marianne; Osler, Merete; Johansen, Christoffer; Frederiksen, Kirsten; Kjær, Susanne K.
Highlights: Possible explanations for an association between socioeconomic position and survival after ovarian cancer were investigated. Data were retrieved from nationwide registers including socioeconomic factors obtained on an individual level. Socioeconomic differences in survival were found mostly among patients diagnosed in an early disease stage. Some survival disparities persisted when taking cancer stage, tumor histology, comorbidity and operation status into account. Findings imply that attention should be paid to socially less advantaged patients during cancer treatment and rehabilitation. Abstract: Aims: In order to reduce social inequality in cancer survival, knowledge is needed about where in the cancer trajectory disparities occur, and how social and health-related aspects may interact. We aimed to determine whether socioeconomic factors are related to cancer diagnosis stage, and whether socioeconomic disparities in survival after ovarian cancer can be explained by socioeconomic differences in cancer stage, comorbidity, treatment or lifestyle factors. Methods: In the Danish Gynaecological Cancer Database we identified 2873 cases of ovarian cancer diagnosed between 2005 and 2010. From this data we retrieved information on prognostic factors, treatment information and lifestyle factors. Age, vital status, comorbidity, education, income and cohabitation status were ascertained from nationwide administrative registers. Associations were analyzed with logistic regression and Cox regression models. Results: Educational level was weakly associated with cancer stage. Short education, lower income and living without a partner were related to poorer survival after ovarian cancer. Among women with early cancer stage, HR (95% CI) for death was 1.75 (1.20–2.54) in shorter compared to longer educated women. After adjustment for comorbid conditions, cancer stage, tumour histology, operation status and lifestyle factors, socioeconomic differences in survival persisted. Conclusions: Socioeconomic disparities in survival after ovarian cancer were to some extent, but not fully explained by differences in important prognostic factors, suggesting further investigations into this problem, however implying that socially less advantaged ovarian cancer patients should receive attention during cancer treatment and rehabilitation.